2020
DOI: 10.1016/s2214-109x(20)30108-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in socioeconomic inequalities in HIV testing: an analysis of cross-sectional surveys from 16 sub-Saharan African countries

Abstract: Background Overall increases in the uptake of HIV testing in the past two decades might hide discrepancies across socioeconomic groups. We used data from population-based surveys done in sub-Saharan Africa to quantify socioeconomic inequalities in uptake of HIV testing, and to establish trends in testing uptake in the past two decades.Methods We analysed data from 16 countries in sub-Saharan Africa where at least one Demographic and Health Survey was done before and after 2008. We assessed the country-specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 23 publications
5
40
1
Order By: Relevance
“…Additionally, we found that people who are more educated, live in urban areas and who are from wealthy homes are more likely to get screened. The role of socioeconomic factors as a driver of HIV testing has been quite well-documented in sub-Saharan African countries [34,35]. These findings underscore the importance of attracting the most vulnerable and at-risk populations to HIV screenings.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we found that people who are more educated, live in urban areas and who are from wealthy homes are more likely to get screened. The role of socioeconomic factors as a driver of HIV testing has been quite well-documented in sub-Saharan African countries [34,35]. These findings underscore the importance of attracting the most vulnerable and at-risk populations to HIV screenings.…”
Section: Discussionmentioning
confidence: 94%
“…Health inequalities that favour the wealthiest subgroups have also persisted in most SSA countries, especially in WCA [6]. Studies found that people with higher socioeconomic position (SEP), and those who were employed, living in urban areas and had heard about HIV and AIDS were associated with better knowledge of HIV status and were more likely to seek testing [7][8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Country sample was based on convenience sampling (data available as of February 2021) that was slightly extended from a previous study [6]. In total, we analysed 10 WCA countries (Burkina Faso, Cameroon, Côte d'Ivoire, Cameroon, Congo DR, Guinea, Liberia, Mali, Niger, Senegal and Sierra Leone) and eight ESA countries (Ethiopia, Kenya, Lesotho, Malawi, Rwanda, Tanzania, Zimbabwe and Zambia).…”
Section: Data and Study Designmentioning
confidence: 99%
“…in sexual health services: chlamydia and gonorrhoea test results [24]). However, sexual health interventions rarely include working-age adults; they are often targeted to students and younger people, likely because they are seen to be vulnerable, lacking the associated health education and more likely to engage in high risk behaviours for contracting sexually transmitted infections [25].…”
Section: Introductionmentioning
confidence: 99%
“…poor diet, smoking, problem alcohol consumption, substance abuse) [27][28][29] and the prevalence of cardiovascular risk and mental ill-health is increasing in construction workers [30][31][32]. HIV infections in adults have long been associated with health inequality, often correlating with the aforementioned risk behaviours [25,33]. Construction workers may be at increased risk for HIV due to occupational hazards [34,35], and migrant workers in the industry may be particularly vulnerable if they are from countries of high HIV prevalence [36,37].…”
Section: Introductionmentioning
confidence: 99%